PENINGKATAN KEAKURATAN INSPEKSI SUBDEPARTMENT QUALITY CONTROL INCOMING : STUDI KASUS - Christian Davin Gunawan; Indriati Njoto Bisono (Jurnal Titra, 2016)
PT. X produces circuit breakers. The raw material inspection process problem is material breakout does not with standard in the production process. These problems affected the inspection accuracy level which is conducted by Quality Control Incoming subdepartment. This research aims to increase the accuration level of the inspection. Analysis using stratification, Pareto diagram, and the cause-effect diagram that shows the biggest problem on visual inspection. The proposal that is proposed and has been tested is a standardization sampling box. The application of the proposal svheme resulted in increasing in April 2016, that is no material break-out. The same result were also achieved in May and June 2016.